Formulation and in vitro Evaluation of Quercetin-Cyclodextrin Tablets - Vijaya Sri, K.; Vijaya Ratna, J. (Asian Journal of Chemistry, 2011)
Quercetin is a natural bioflavonoid and it exhibits antiinflammatory, antioxidant and antitumor activities. However, because of its poor solubility and low oral bioavailability, the development of an orally bioavailable flavonoid-carrier system is of great importance clinically. Consequently, the rationale of this study quercetin by preparing its formulations with enhanced dissolution rate. Inclusion complexes of quercetin with cyclodextrins like β-cyclodextrins (βCD), hydroxyl propyl β-cyclodextrins (HP-βCD) and sulfa butyl β-cyclodextrins (SBE-βCD) were prepared by physical mixing and kneading method. Quercetin-CD (1:2) tablets were prepared by direct compression method. QT-βCD tablets exhibited higher dissolution rate than QT/QT-HP-βCD/ QT-SBE βCD.